Distance Education: Imbalance between Possibilities and Threats - D. А. Endovitsky; I. E. Risin; Yu. I. Treshchevsky; E. A. Rudnev (Moscow Polytechnic University, 2022)
Purpose: To quantify the opportunities and threats arising from the spontaneous expansion of distance learning in the wake of the pandemic and measures to counteract its spread.Research methods: ex-pert analysis, fuzzy logic, comparative analysis.Results and conclusions. The analysis of three groups of experts' opinions: employers, university professors and students showed not-high values of revealed possibilities, connected with distance learning. Among them the average level of assessment reached: the increase of the level of computer literacy and the possibility of learning without disconnecting from the main activity in any geographical location. The latter opportunity is given more importance by employers than by teachers and students. Many threats of distance learning are evaluated as having a very high and high importance. The highest level of threat of reduction of the level of practical knowledge is marked by all expert groups. Almost the same level of significance was assigned by all expert groups to the negative impact of long-term computer use on students' health. Opinions of expert groups differ with regard to other threats. Employers are the most cautious about them, they single out several other significant threats connected with the learning process - decrease of emotional component of the educational process and teachers' lack of mastery of computer technologies which does not provide transfer of the necessary amount of information to students. Teachers and students assess these threats as less significant. The threats noted actualize the need to: strengthen the practical orientation of training in both distance and face-to-face format, expanding the competence of teaching staff in the field of computer technology, developing a system to counteract the negative impact of long-term use of computers on the health of students.